2018
DOI: 10.1016/j.chemosphere.2018.01.154
|View full text |Cite
|
Sign up to set email alerts
|

Survey of 218 organic contaminants in groundwater derived from the world's largest untreated wastewater irrigation system: Mezquital Valley, Mexico

Abstract: The Mezquital Valley system is the world's oldest and largest example with regard to use of untreated wastewater for agricultural irrigation. Because of the artificial high recharge associated with the Mezquital Valley aquifers, groundwater is extracted for human consumption, and there are plans to use this groundwater as a water resource for Mexico City. Thus, this study analyzed 218 organic micro-contaminants in wastewater, springs, and groundwater from Mezquital Valley. Five volatile organic compounds (VOCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
7

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(69 citation statements)
references
References 60 publications
0
58
0
7
Order By: Relevance
“…These characteristics surely allowed the compound to be detected in the GW samples. On the other hand, although acetaminophen was detected in this case, [80] showed that acetaminophen was degraded and not detected in GW, but they did not specify the soil types. In 2002, [81] pointed out that both primidone and carbamazepine were particularly useful for GW studies because both were detected.…”
Section: Ecs Suggested To Be Indicators Of Reclaimed Water Arrival Inmentioning
confidence: 73%
“…These characteristics surely allowed the compound to be detected in the GW samples. On the other hand, although acetaminophen was detected in this case, [80] showed that acetaminophen was degraded and not detected in GW, but they did not specify the soil types. In 2002, [81] pointed out that both primidone and carbamazepine were particularly useful for GW studies because both were detected.…”
Section: Ecs Suggested To Be Indicators Of Reclaimed Water Arrival Inmentioning
confidence: 73%
“…The wastewater recharge rate in the study area is approximately 25 m 3 /s, and corresponds to 13.3 times the natural recharge rate in the Mezquital Valley [12]. The accelerated recharge rate facilitates the transport of persistent pollutants to the unconfined aquifer, and results in a deleterious impact on groundwater quality [13]. Previous studies have reported the pollution of groundwater related to high levels of NO 3…”
Section: Introductionmentioning
confidence: 91%
“…The raw wastewater that is sent from Mexico City (through the "Emisor Central") is used for agricultural irrigation in Tula Valley, and presents traces (ng/L) of at least 18 OMPs. Overall, in spite of the occurrence of some hard to degrade compounds in the groundwater of the Mezquital Valley aquifers, soil layers with a high content of organic matter and clays seem to act as filter and buffer systems for almost all of these compounds, which prevent contamination of the aquifer [18,28,43]. In addition, carbamazepine was regularly recorded, which suggests the possible presence of other polar and persistent organic micro-pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, few works have evaluated the content of these organic contaminants in wastewater and groundwater in the same area. Those that did measured very few compounds [18]. They tended only to assess the occurrence and fate of semi-volatile organic compounds, pharmaceutically active compounds, and other emerging contaminants in the Tula Valley and focused on their accumulation and dissipation, or their sorption/desorption from soils [18].…”
Section: Introductionmentioning
confidence: 99%